CHARACTERISTICS OF THE QUAIL CEMENT - Lesmono, Drystiana Yessi Ayu; Trilaksana, I Gusti Ngurah Bagus; Bebas, Wayan (Buletin Veteriner Udayana, 2017)
This study aims were to investigate the characteristics of the quail cement macroscopically and microscopically. The research used 30 quail with ± 6 weeks of age as a source of cement. The quail cement collection were done by using modifications of massage technique to prevent contamination of the foam produced by cloaca gland and feces. Examination of cement macroscopically include volume, color, pH and consistency (viscosity) and microscopic examination includes sperm concentration, morphology, abnormalities , the number of live sperm and sperm motility. The results showed that the quail cement ( Coturnix-Coturnix Japonic ) macroscopically has a ±0.02 ml of volume, beige, pH ±7.06, lumpy consistency and a distinctive odor, while the results of microscopic examination of quail has a mass wave of spermatozoa good (++), ±86% progressive motility, sperm concentration ±57.2x107, spermatozoa abnormalities ±7.4% and ±5% spermatozoa death.
Keywords: Burung puyuh; karakteristik semen; pemeriksaan makroskopik; pemeriksaan mikroskopik